Algorithms and Autonomy The Ethics of Automated Decision Systems - Rubel, Alan (Social Sciences, 2021)
Algorithms influence every facet of modern life. However, delegating important decisions to machines gives rise to deep moral concerns about responsibility, transparency, fairness, and democracy. This book examines these concerns by connecting them to the human value of autonomy. This title is also available as Open Access on Cambridge Core.